(untitled) - McAuslan, Patrick (Aldershot, Hants, England, 2003)
Bringing together the two fields of land reform and law, this volume examines the role the law and lawyers can, should and do play in developing countries in the evolution of land policies, in land tenure reform, and in the reform of land use and urban planning. Providing both a theoretical and practical perspective it discusses the role of law in both urban land reform, concentrating on reforms in land use and town and country planning law, and general national land reform, looking at specific case studies and at more general themes. It aims to provide a coherent set of ideas and philosophies about land reform through the medium of law, which have been developed through reflection and action over a considerable period of time.
Keywords: Land use,English-speaking countries; Law and legislation,Colonial influence; Developing countries